The potential of arfak rainbowfish Melanotaenia arfakensis Allen 1990 as biocontrol of mosquito larvae - Emmanuel Manangkalangi; Simon P. O. Leatemia; Paskalina Th. Lefaan; Hans F. Z. Peday; Luky Sembel (Jurnal Iktiologi Indonesia, 2015)
Research on the potency of arfak rainbowfish as a biocontrol of mosquito larvae was held in Fisheries Laboratory FPPIK, the Universitas Negeri Papua from August to November 2013. The aim of this study was to describe the potency of arfak rainbowfish as a biocontrol of mosquito larvae and compared it with two introduction fish species, Gambusia affinis and Aplocehilus panchax. All of the three species collected from Prafi River, Manokwari were acclimatized for one month in the laboratory. Male individuals were selected and grouped into four size classes according to body length. Three individuals were chosen to represent each species in each size class. Each individual was treated with mosquito larvae (stage IV instars and pupae) of 100 individuals separately, as well as 50 individual instars and pupae simultaneously. The level of predation and selectivity of both prey types was recorded, within 15-minute observation period. All of the three species showed levels of predation on instars and pupae increased with increasing body size. The level of predation on instars was higher than the pupae when the two treatment preys were treated separately. Furthermore, the predation level of arfak rainbowfish on instars and pupae higher than the other two fish species in all size classes, and also the relative degree of selectivity did not differ between the two types of prey in each size class. These results as well as other criteria, indicates M. arfakensis has potential as a biocontrol agent to mosquito larvae. Abstrak Penelitian potensi ikan pelangi arfak sebagai biokontrol larva nyamuk dilaksanakan di laboratorium Laboratorium Perikanan FPPIK Universitas Negeri Papua pada bulan Agustus sampai November 2013. Tujuan penelitian ini untuk mendeskripsikan potensi ikan pelangi arfak sebagai biokontrol larva nyamuk dan membandingkannya dengan dua spesies ikan introduksi Gambusia affinis dan Aplocheilus panchax. Ketiga spesies ini dikoleksi dari daerah aliran Sungai Prafi, Manokwari yang diaklimatisasi selama satu bulan di laboratorium. Dipilih individu jantan dan dikelompokkan berda-sarkan panjang tubuh ke dalam empat kelas ukuran. Tiga individu dipilih mewakili setiap spesies dan kelas ukuran. Setiap individu diberi perlakuan dengan larva nyamuk (tahap instar IV dan pupa) sebanyak 100 individu secara terpisah, serta 50 individu instar dan pupa secara bersamaan. Tingkat pemangsaan dan pilihan kedua tipe mangsa ini dicatat, waktu pengamatan 15 menit. Ketiga spesies menunjukkan tingkat pemangsaan terhadap instar dan pupa semakin meningkat dengan sema-kin besarnya ukuran tubuh, tingkat pemangsaan terhadap instar lebih tinggi dibandingkan pupa pada perlakuan pemberian kedua mangsa secara terpisah. Selanjutnya, tingkat pemangsaan ikan pelangi arfak terhadap instar dan pupa lebih tinggi dibandingkan kedua spesies ikan lainnya pada semua kelas ukuran, serta tingkat pilihan yang relatif tidak berbeda di antara kedua tipe mangsa pada setiap kelas ukuran. Hasil penelitian ini dan juga kriteria lainnya, menunjukkan bahwa ikan pelangi arfak memiliki potensi sebagai agen biokontrol terhadap larva nyamuk.